2009
DOI: 10.1378/chest.08-2697
|View full text |Cite
|
Sign up to set email alerts
|

Soluble P-Selectin and the Risk of Primary Graft Dysfunction After Lung Transplantation

Abstract: Background: Platelet activation with subsequent neutrophilic adherence to the vasculature initiates ischemia-reperfusion injury. We hypothesized that higher plasma P-selectin levels reflecting platelet activation would therefore be associated with primary graft dysfunction (PGD) after lung transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…The mechanistic underpinnings of the increased risk of PGD among patients with IPF and PAH include greater endothelial injury from hemodynamic forces in addition to inherent abnormalities in coagulation /infl ammation, platelet activation, and cell adhesion observed in transplant recipients with both elevated mPAP and PGD. 22,23,26 Furthermore, vasoactive mediators such as endothelin-1, platelet-derived growth factor, transforming growth factor-b , and fi broblast growth factor have all been implicated in the pathogenesis of IPF, and these mediators can also contribute to the development of lung injury. [27][28][29][30] In addition to raising questions about the shared pathophys iologic characteristics of secondary PAH and PGD, our study may have direct clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanistic underpinnings of the increased risk of PGD among patients with IPF and PAH include greater endothelial injury from hemodynamic forces in addition to inherent abnormalities in coagulation /infl ammation, platelet activation, and cell adhesion observed in transplant recipients with both elevated mPAP and PGD. 22,23,26 Furthermore, vasoactive mediators such as endothelin-1, platelet-derived growth factor, transforming growth factor-b , and fi broblast growth factor have all been implicated in the pathogenesis of IPF, and these mediators can also contribute to the development of lung injury. [27][28][29][30] In addition to raising questions about the shared pathophys iologic characteristics of secondary PAH and PGD, our study may have direct clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…LTOG is an NHLBI-funded prospective cohort study of lung transplant recipients with the primary aim of examining clinical and genetic risk factors for PGD at nine United States centers (a full list of investigators and participating centers appears before the REFERENCES section) (22)(23)(24)(25)(26)(27)(28). Based on a reported association between obesity and early mortality after lung transplantation for COPD and ILD (21), we restricted our study sample to 512 adult LTOG participants with COPD or ILD who underwent single or bilateral lung transplantation between March 2002 and July 2009 and who had complete exposure and outcome data.…”
Section: Methods Study Design and Participantsmentioning
confidence: 99%
“…Twenty-nine patients (28%) developed grade 3 PGD within the first 72 hours. The median CC16 level 6 hours after transplant was significantly higher in patients with PGD (13.8 ng/ml (IQR 7.9, 30.4 ng/ml)) than in patients without PGD (8.2 ng/ml (IQR 4.5,19.1 ng/ml)), p = 0.02. Elevated CC16 levels were associated…”
Section: Introductionmentioning
confidence: 89%
“…Biomarker studies have suggested important mechanistic pathways in clinical PGD (12)(13)(14)(15)(16)(17)(18)(19). Injury to the distal airway epithelium is a common finding in PGD and acute lung injury (ALI).…”
Section: Introductionmentioning
confidence: 99%